An uncertainty principle for star formation: II. A new method for characterizing the cloud-scale physics of star formation and feedback across cosmic history - Kruijssen, Diederik; Hygate, Alexander P. S.; Haydon, Daniel T. (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. The cloud-scale physics of star formation and feedback represent the main uncertainty in galaxy formation studies. Progress is hampered by the limite
Gesehen am 11.02.2019